IMPLEMENTASI BEST PRACTICE EKSTRAKURIKULER ANGKLUNG UNTUK MENINGKATKAN PARTISIPASI DAN APRESIASI SENI SISWA SD MUHAMMADIYAH KRONGGAHAN SLEMAN - Azhar Nur Firdaus; Dhiniaty Gularso (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The low level of students’ participation and appreciation of art at the elementary school level remains a challenge in arts education, particularly in traditional music learning. Arts instruction that is limited to intramural activities often fails to provide meaningful and sustainable learning experiences for students. One effort to address this issue is through culture-based extracurricular activities, such as angklung. This study aims to describe the implementation of best practices in angklung extracurricular activities to enhance students’ participation and art appreciation at SD Muhammadiyah Kronggahan. This research employed a descriptive qualitative approach. Data were collected through observations, interviews, and documentation involving extracurricular instructors, students, school administrators, and related stakeholders. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings indicate that the implementation of best practices in angklung extracurricular activities supported by mandatory participation policies, regular practice schedules, certified instructors, adequate facilities, and strong support from parents and the community successfully increased students’ active participation and fostered their appreciation of art and local culture. These outcomes were also reflected in students’ consistent achievements in various regional competitions. Therefore, well-managed and professionally implemented angklung extracurricular activities can serve as a model of best practice for strengthening arts education in elementary schools.